2020
DOI: 10.2147/idr.s239095
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Systematic Review of Vancomycin Dosing in Patients with Hematologic Malignancies or Neutropenia</p>

et al.

Abstract: Objective: To provide a comprehensive review of vancomycin dosing in patients with hematologic malignancies or neutropenia. Methods: PubMed, Embase and the Cochrane Library were searched through April 2, 2020. Original studies relevant to vancomycin dosing regimen in adults with hematologic malignancies or neutropenia were included. No restriction was applied in study design and language. A descriptive analysis was performed. Results: Twenty-three studies were included eventually, of which eighteen were case s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Patients with altered V d and renal function and those with unstable haemodynamics might be candidates for AUC-guided dosing to increase the prediction accuracy [ 42 , 52 , 96 , 117 , 118 , 119 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 ] (III-A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with altered V d and renal function and those with unstable haemodynamics might be candidates for AUC-guided dosing to increase the prediction accuracy [ 42 , 52 , 96 , 117 , 118 , 119 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 ] (III-A).…”
Section: Resultsmentioning
confidence: 99%
“…Augmented renal clearance [ 127 ] is experienced by patients with sepsis [ 128 , 129 , 130 ]. Enhanced clearance is also observed in patients with hematopoietic tumours or febrile neutropaenia [ 131 ]. Furthermore, patients with heart failure [ 132 , 133 ], oedema [ 132 , 134 ], dehydration [ 117 , 119 ], burns [ 135 , 136 ], obesity [ 137 , 138 , 139 , 140 ], or emaciation [ 140 ] have different V d and clearance from individuals in the normal population.…”
Section: Discussionmentioning
confidence: 99%
“…Febrile neutropenia is reported to promote renal blood flow due to enhanced cardiac output, which leads to enhanced renal clearance of drugs, such as vancomycin relative to bodyweight and decreased serum drug concentrations. 13 In this study, the effect of febrile neutropenia on vancomycin concentration/dose ratio and vancomycin clearance in pediatric patients stratified by age was evaluated. Compared with those in the nonfebrile neutropenia cohort, eGFR and vancomycin clearance were significantly higher, and the vancomycin concentration/dose ratio was significantly lower in the febrile neutropenia cohort.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review indicated that a conventional dose of vancomycin leads to suboptimal blood concentrations in patients with hematological malignancies or neutropenia. 13 Similarly, another study suggested that vancomycin clearance in pediatric patients with febrile neutropenia increases due to ARC. 14 However, the authors analyzed all pediatric subjects aged 1-14.7 years without age stratification.…”
Section: Introductionmentioning
confidence: 98%
“…A systemic review conducted in 2020 by He et al confirmed that the current conventional vancomycin protocol is accompanied by a low sub-therapeutics trough in patients with hematological malignancy or neutropenia. The mechanism by which neutropenia induces the sub-therapeutic level is not well understood ( He et al, 2020 ); However, other studies explained this sub-therapeutic level due to the high volume of distribution and clearance in a neutropenic patient ( Hochart et al, 2011 , Guilhaumou et al, 2016 ). Neutropenia can cause the augmentation of vancomycin clearance, and many hypotheses exist to explain that, including; i) kidney function and urine output can be altered by cancer and excessive hydration, ii) induction of non-renal metabolism of vancomycin such as hepatic elimination by conjugation, and iii) vascular permeability is enhanced by infection and neutropenia, which leads to extravasations of vancomycin and caused decreased serum concentration ( Al-Kofide et al, 2010 , Choi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%